Temozolomide hexadecyl ester targeted plga nanoparticles for drug-resistant glioblastoma therapy via intranasal administration - Siqi Wang; Yawen Yu; Aiping Wang; Xinliu Duan; Yuchen Sun; Liangxiao Wang; Liuxiang Chu; Yanan Lv; Nan Cui; Xuesong Fan; Chunjie Sha; Lixiao Xu; et al. (Frontiers Media S.A., 2022)
Introduction: Temozolomide (TMZ) is the first-line drug for glioblastoma (GBM), but it is limited in clinical use due to the drug resistance, poor brain targeting, and side effects. Temozolomide hexadecyl ester (TMZ16e), a TMZ derivative with high lipophilicity, membrane permeability, and high anti-glioma properties, has the potential to reverse drug resistance. In this study, anti-ephrin type-A receptor 3 (EphA3) modified TMZ16e loaded nanoparticles (NPs) were prepared for targeted GBM therapy via intranasal administration to deliver TMZ16e to the brain, treat drug-resistant glioma effectively, and reduce peripheral toxicity.Methods: TMZ16e loaded NPs were prepared by emulsion solvent evaporation method followed by modified with anti-EphA3 (anti-EphA3-TMZ16e-NPs). In vitro evaluations were performed by an MTT assay and flow cytometry analysis. The orthotopic nude mice models were used to evaluate the anti-glioma effect in vivo. Additionally, we investigated the anti-drug resistant mechanism by western blot analysis.Results: The particle size of the prepared NPs was less than 200 nm, and the zeta potential of TMZ16e-NPs and anti-EphA3-TMZ16e-NPs were -23.05 ± 1.48 mV and -28.65 ± 1.20mV, respectively, which is suitable for nasal delivery. In vitro studies have shown that anti-EphA3 modification increased the cellular uptake of nanoparticles in T98G cells. The cytotoxicity in the anti-EphA3-TMZ16e-NPs treated group was significantly higher than that of the TMZ16e-NPs, TMZ16e, and TMZ groups (p < 0.01), and the cell cycle was blocked. Western blotting analysis showed that the TMZ16e-loaded NPs were able to effectively downregulate the expression level of O6-methylguanine-deoxyribonucleic acid-methyltransferase (MGMT) protein in T98G cells and reverse drug resistance. In vivo studies showed that the median survival time of tumor-bearing nude mice in the anti-EphA3-TMZ16e-NPs group was extended to 41 days, which was 1.71-fold higher than that of the saline group and the TUNEL staining results of the brain tissue section indicated that the TMZ16e-loaded NPs could elevate apoptosis in T98G cells.Conclusion: In conclusion, the TMZ16e-loaded NPs can be effectively delivered to the brain and targeted to gliomas, exhibiting better anti-glioma activity, indicating they possess great potential in the treatment of drug-resistant glioma.